Building Legal Awareness: Solutions to Land Disputes and Family Harmony - Tumini Tumini (TGO Journal of Community Development, 2023)
The aim of the community service activity, Real Work Lecture, community empowerment learning in Jrebeng Kidul Village, Probolinggo City, is to try to build legal awareness in the community starting from the smallest sphere, namely the family. This service activity takes the form of socialization or legal counseling on how to respond to problems in the surrounding environment by being aware of the levels of rights and obligations so that a peaceful and orderly sub-district can be created, especially in land disputes. The impact of this service activity is able to grow and increase legal awareness for individuals, families and local residents so that order and order and harmony are created in social interactions in Jrebeng Kidul Village. The result of this service activity is the formation of community groups who care and are aware of the law. The benefit of this community service is to build community awareness to live in an orderly, peaceful and peaceful manner as well as legal protection, especially for the people of Jrebeng Kidul Village.